Research methods in sport - Smith, Mark F. (Sage, 2018)
Packed full of essential tools and tips, this second edition is your quick-start guide to undertaking research within the real world of sport. Using clear, accessible language, Smith maps an easy-to-follow journey through the research process, drawing upon the most up-to-date evidence and resources to help you select the most appropriate research approach for your project. Through out the book you will discover: Key points that highlight important definitions and theories; Reflection points to help you make connections between key concepts and your research; Learning activities to put your newfound knowledge into practice; Further reading to explore the wider context of sport research in the real world. Featuring over 35 case studies of students' and academics' research in practice, this book is the perfect-by-your-side to have during your own sport research.